Pengaruh Self Efficacy dan Locus of Control terhadap Komitmen Organisasional Relawan Covid-19 di SRPB Kota Pasuruan - M. Rifqi Fakhar; Fien Zulfikarijah; Sandra Irawati (Pustaka Peradaban, 2022)
Human resources are a significant aspect of the progress and success of organizations in the current era of globalization. A dynamic world requires organizations to be more adaptive. It makes human resources a driving element whose organizational commitment is significant to maintain and improve at this time, covid-19 is the main focus of the government's attention to reducing the rate of spread of covid-19. Covid-19 is a major problem in the health sector and is of particular concern to many people, including volunteer organizations. Volunteer commitment is different from employees, and volunteer commitment is more influenced by internal or personal factors volunteers. This study aims to determine the organizational commitment of COVID-19 volunteers at SRPB Pasuruan City through personality variables, namely self-efficacy and locus of control. This research is in the form of quantitative research. The sample of this study was the Covid-19 volunteers at the Pasuruan City SRPB, totaling 180 volunteers. With multiple linear regression analysis models and using SPSS 25 analysis tool. The results of this study are Self Efficacy has a positive and significant effect on organizational commitment, Locus of control has a positive and significant effect on organizational commitment, Self Efficacy and locus of control have a positive and significant effect on organizational commitment. Professional commitment and self-efficacy variable has a stronger effect on organizational commitment than a locus of control. Sumber daya manusia adalah aspek penting dalam kemajuan dan kesuksesan organisasi dalam era globalisasi saat ini. Dunia yang dinamis menuntut organisasi untuk lebih adaptif. Hal ini menjadikan sumber daya manusia menjadi unsur penggerak yang komitmen organisasionalnya sangat penting untuk dipertahankan dan ditingkatkan pada masa sekarang ini covid-19 menjadi fokus perhatian utama pemerintah untuk mengurangi laju penyebaran covid-19. Covid-19 merupakan masalah utama dalam bidang kesehatan dan menjadi perhatian khusus bagi banyak orang termasuk organisasi relawan. Komitmen relawan berbeda dengan karyawan, dan komitmen relawan lebih dipengaruhi oleh faktor internal atau personal dari diri relawan. Penelitian ini bertujuan untuk mengetahui komitmen organisasional pada relawan covid-19 di SRPB Kota Pasuruan melalui variabel kepribadian yaitu self efficacy dan locus of control. Penlitian ini berbentuk penelitian kuantitatif. Sampel dari penelitian ini adalah relawan covid-19 di SRPB Kota Pasuruan yang berjumlah 180 relawan. Dengan model analisis regresi linear berganda dan menggunakan alat analisis SPSS 25. Hasil dari penelitian ini adalah Self Efficacy berpengaruh positif dan signifikan terhadap komitmen organisisasional, Locus of control berpengaruh positif dan signifikan terhadap komitmen organisisasional, Self Efficacy dan locus of control berpengaruh positif dan signifikan terhadap komitmen profesional,variabel self efficacy berpengaruh lebih kuat terhadap komitmen organisasional dibandingkan locus of control.